Development of a decentralized multi-axis synchronous control approach for real-time networks. (May 2017) - Xu, Xiong; Gu, Guo-Ying; Xiong, Zhenhua; Sheng, Xinjun; Zhu, Xiangyang
Abstract: The message scheduling and the network-induced delays of real-time networks, together with the different inertias and disturbances in different axes, make the synchronous control of the real-time network-based systems quite challenging. To address this challenge, a decentralized multi-axis synchronous control approach is developed in this paper. Due to the limitations of message scheduling and network bandwidth, error of the position synchronization is firstly defined in the proposed control approach as a subset of preceding-axis pairs. Then, a motion message estimator is designed to reduce the effect of network delays. It is proven that position and synchronization errors asymptotically converge to zero in the proposed controller with the delay compensation. Finally, simulation and experimental results show that the developed control approach can achieve the good position synchronization performance for the multi-axis motion over the real-time network. Abstract : Highlights: In this paper, we propose a decentralized synchronous controller for each motion control node to achieve the position synchronization of real-time network-based systems. Simulations and experiments are conducted to demonstrate the effectiveness of the proposed synchronization control approach in the real-time network. The distinct features of the work are summarized as follows. We extend the position synchronization approach to the networked multi-axis motion control system. A decentralized synchronous controller, which takes the message scheduling of the network into account, is designed to synchronize its motion with other nodes. Moreover, in order to reduce the effect of network-induced delays, a motion message estimator is utilized in the synchronous controller to estimate the current position errors of preceding axes. It is proven that the decentralized synchronous controller with the delay compensation is asymptotically stable. A networked simulation system is developed through the Matlab/Simulink and the TrueTime toolbox, and an experimental platform is built based on smart networked motion control nodes and the real-time Ethernet communication. Then, simulations and experiments are conducted to verify the effectiveness of the proposed synchronization control approach. Both simulation and experimental results demonstrate that the decentralized synchronous controller achieves good position synchronization performance in the networked multi-axis motion control system.